Analisis Kesalahan Siswa dalam Menyelesaikan Soal-Soal Pada Materi Geometri Berdasarkan Taksonomi SOLO Kelas VII MTs Muhammadiyah Tanetea - Arimbi Puspa Mega; Thamrin Tayeb; Andi Dian Angriani; Lisa Kurnia Syam; Rustiani (Department of Mathematics Education, 2023)
This study aims to analyze students' errors in solving questions on geometry material based on the SOLO taxonomy for class VII MTs Muhammadiyah. The research method used is qualitative research. The method of data collection was the test method, which involved giving questions to 31 class VII students of MTs Muhammadiyah Tanetea and conducting in-depth interviews with five (five) respondents who were selected by the researcher based on the level of response obtained by the students. The results show that the proportion of student response levels is as follows: as much as 61.3% of the total students are at the prestructural response level; 25.8% are at the unstructural response level; 12.9% are at the multistructural response level; and there were no students who were at the rational response level or extended abstract response level. It was concluded that class VII MTs students were at the prestructural response level.